ENHANCING TEACHERS’ PROFESSIONAL COMPETENCIES FOR HYBRID LEARNING THROUGH A PEER-LED DIGITAL MENTORSHIP PROGRAM - Rafiullah Amin; Rachel Chan; Megan Koh (Journal Neosantara Hybrid Learning, 2025)
The rapid shift toward hybrid learning has underscored the urgent need to enhance teachers’ digital pedagogical competencies. Many educators, particularly in developing educational contexts, face challenges in integrating technology effectively into instructional design and collaborative teaching practices. This study investigates the implementation of a peer-led digital mentorship program as a sustainable approach to strengthen teachers’ professional competencies for hybrid education. The research aims to examine how structured peer mentoring, supported by digital platforms, improves teachers’ skills in instructional technology, online communication, and collaborative curriculum development. A mixed-method design was applied, involving 60 teachers from secondary schools participating in a three-month mentorship program. Quantitative data were collected through pre- and post-training competency assessments, while qualitative insights were derived from focus group discussions and reflective journals. Data analysis employed paired-sample t-tests for statistical validation and thematic analysis for narrative interpretation. Results showed significant improvement in teachers’ digital literacy (p < 0.01), confidence in hybrid instruction, and collaborative engagement. Participants reported that peer mentoring provided psychological safety, practical modeling, and contextual learning experiences that formal training often lacked. The study concludes that peer-led digital mentorship represents an effective, scalable model for professional development in the hybrid learning era. It fosters a culture of collaboration, adaptability, and continuous learning among teachers, supporting the long-term sustainability of hybrid education practices.